Observation of collective bistability in an ultracold cloud of strongly driven strontium atoms interacting with a ring cavity - Jerez, Yajaira Dalila Rivero (2022)
We report on our progress in the construction of a machine capable of cooling Strontium atoms to ultra-cold temperatures, to interact collectively with the modes of a ring cavity. We present the first observation of a novel manifestation of saturation-induced optical bistability in a resonantly pumped optical ring cavity, interacting with a narrow atomic transition cloud. The bistability emerges, above a critical pump rate, as an additional peak in the cavitys normal-mode spectra near the atomic resonance. The new regime addressed for our machine takes advantage of the narrow atomic transition enabling the observation of bistability in a strong resonant regime where the atoms couple collectively to the cavity.